Decolonizing Language Teachers’ Teaching Practices through a Postmethod Pedagogy - Avella Alvarado, Adriana Milena; León Lozada, Geidy Yohana (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article presents a critical and theoretical reflection upon a pedagogical proposal which considers an EFL teaching practice. The target pedagogical experience relies on the first step to starting decolonizing language teachers’ teaching practices in the context they live in. Understanding that decolonizing teaching practices is a continuous process of reflection that involves decision-making, awareness of the students’ needs, and the context in which they are immersed. Firstly, the document will present some of the authors’ insights about language policies as the National Bilingual Program (PNB). Secondly, the manuscript addresses the teaching approach in which the proposed activities are embedded as a means to stress the necessity to start decolonizing pedagogical practices. Thirdly, the manuscript delves into Kumaravadivelu’s particular perspectives of Method and Post method pedagogy in language teaching. Finally, there will be some reflections about what language teachers do for engaging students in their own language learning providing meaningful practices, and what they have constructed about decolonization.